'In common for everyone': shared space and private possessions in the English parish church nave. Issue 2 (15th March 2019) - Byng, Gabriel
ABSTRACT: Medieval historians have long emphasised the social significance of the installation of fixed and owned seats in English parish churches, but its impact was affective and ideological too. Since the late thirteenth century, church authorities had decreed that all worshippers should have equal access to the nave but seating introduced an object with many of the characteristics of private property into space theoretically held in common. Judges and bishops not only rued this as a corruption of Christian egalitarianism but also feared the opportunities for sensory enrichment, privacy and conflict that came with purchased pews. A new proprietary culture developed in churches that stimulated new practices, affective bonds and ideas about how entitlements and hierarchies from parochial life should or could be transplanted into the nave space.